Education as a catalyst for the social inclusion of people with learning disabilities. (15th November 2021) - Robinson, Deborah; Codina, Geraldene; Strogilos, Vasilis; Dimitrellou, Eleni
Accessible summary: The social inclusion of people with learning disabilities is an important topic because we all have a right to participate in society. Articles in this special issue talk about how education can help to make social inclusion better so that people with learning disabilities can join in and belong, just like everyone else. The articles talk about how changes in the way people think about learning disabilities can help make education better at making social inclusion happen. They also talk about how this can happen by supporting transitions to adulthood (e.g., into paid work), learning in universities and getting people with learning disabilities involved in writing courses about health.